1977
DOI: 10.1001/archderm.113.11.1518
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A10 in pemphigus among Japanese

Abstract: The frequency of the major histocompatibility antigen, HLA-A10, was significantly increased (corrected P less than .025) in 43 unrelated patients with pemphigus vulgaris (41.9%) and in 25 patients with pemphigus foliaceus (48.0%), when compared with 60 unrelated healthy controls (16.7%). No significant correlations with other HLA or differences between pemphigus vulgaris and pemphigus foliaceus were observed. Both forms of pemphigus were considered to link with the HLA-A10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…25 Former studies have shown a higher prevalence of HLA-A10 and HLA-A13 haplotypes in the Jewish and non-Jewish population. [26][27][28] On the molecular level, the specific polymorphism in PV was found to be linked to the DQw1 alleles in DR4 patients and to DQw3 alleles of the HLA-D region in DRw6 patients. 29 With the use of the restriction fragment length polymorphism (RFLP) technique, Hispanic siblings were found to express identical DR4 haplotypes and DQw3.2 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…25 Former studies have shown a higher prevalence of HLA-A10 and HLA-A13 haplotypes in the Jewish and non-Jewish population. [26][27][28] On the molecular level, the specific polymorphism in PV was found to be linked to the DQw1 alleles in DR4 patients and to DQw3 alleles of the HLA-D region in DRw6 patients. 29 With the use of the restriction fragment length polymorphism (RFLP) technique, Hispanic siblings were found to express identical DR4 haplotypes and DQw3.2 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, A26 (10) and B38(16) have a higher frequency among Ashkenazi Jewish PV patients (Krain et al 1973, David et al 1981, Park et al 1979, Brautbar et al 1980, Amar et al 1984. In Japanese, both PV and PF were found to be associated with DR4 (Matsuyama et al 1981) and A26(10) (Hashimoto et al 1977). Sakurai et al (1981), however, found a negative association of PV and DR2, an antigen absent in their patients.…”
mentioning
confidence: 96%
“…From our early data (Hashimoto et al 1977), HLA-A26, though not as strong as DR4, had an excess frequency in pemphigus patients in Japan, which showed that HLA-DR antigens are more strongly associated with certain diseases rather than HLA-A, -B or -C antigens. This relationship suggested that immune response genes or disease susceptibility genes might exist closely in a HLA-DR region.…”
Section: Discussionmentioning
confidence: 83%